The Use of “Ná” and “Hold” Verbs by Bilingual PreSchool Children in Singapore - Yap, Ying Tong (2017)
Verb forms a major category of lexicon in any language. As our daily actions consist of mostly hand actions, it is important for bilingual speakers to be able to use different specific hand action verbs to describe the corresponding actions. This study focuses on one particular type of hand action, namely, holding actions, to examine Singaporean bilingual preschoolers’ competencies in both English and Mandarin through their usage of holding verbs.